Dysregulation of mitochondria-lysosome contacts by GBA1 dysfunction in dopaminergic neuronal models of Parkinson’s disease - Soojin Kim (Nature Portfolio, 2021)
Mitochondria-lysosome contact sites mediate cross-talk between the two organelles. Here, the authors show mitochondria-lysosome contacts are prolonged and defective in heterozygous mutant GBA1 neurons, which is caused by defective modulation of TBC1D15 due to decreased GBA1 activity.